The Impact of Inclusion on Organizational Citizenship Behavior - Hamdan, Lara (2023)
Purpose – This research aims to study the relationships between inclusion, diversity management and organizational citizenship behavior. It also aims at exploring the role of diversity management in the workplace as a mediator. Our attempt is to examine the importance of inclusion and diversity management in initiating organizational citizenship behaviors in employees. To add to prior literature and to fill gaps as recommended, this study aims at examining the different dimensions of inclusion and diversity management. In addition, we will be examining two different contexts; Lebanon and the MENA region and this will enable us to compare the results and formulate a better picture on the current workplace status regarding our study. We aim to ensure that our findings indicate the direct relationship between inclusion, diversity management and organizational citizenship behavior, and how diversity management serves as a mediator between inclusion and organizational citizenship behavior. Methodology – A total of 498 working employees were sent on a 24 close–ended questionnaire divided into 4 sections which were measured using a 5-point scale. Findings – Findings indicate that the model’s direct relationships were supported between Inclusion, Diversity Management and Organizational Citizenship Behavior. In addition, results have also reported the mediating effect of Diversity Management between Inclusion and OCB. Practical implications – Organizations should give priority to inclusive practices including granting equal chances and developing a sense of belonging.